A CONSUMER BUYING BEHAVIOR WHILE PURCHASING LAPTOPS IN TIRUPATTUR TOWN - Saravanan, M. (International Journal of Research -GRANTHAALAYAH, 2016)
The technology is changing so fast with the development of computer hardware. It has observed that last two decade the purchase of laptop has increased significantly. Now laptop purchase is feeling like purchases of fast moving consuming item. This signifies that the people are very much interested to handle technological instruments in their day to day activities. The laptop is the main sources of communication worth intra and intercommunication among the people. The laptop companies in Tirupattur are interested to study the buying behavior while purchasing towards laptop. In order to develop a framework for the study consumer behavior it is helpful to begin by considering the evolution of the field of consumer research and the different paradigms of thought that have influenced that discipline. As describe in this article, a set of dimensions can be identified in the literature, which can be used to characterize and differentiate, the various perspective on consumer research.